Silicified cell walls as a defensive trait in diatoms. Issue 1901 (24th April 2019) - Pančić, Marina; Torres, Rocio Rodriguez; Almeda, Rodrigo; Kiørboe, Thomas
Abstract : Diatoms contribute nearly half of the marine primary production. These microalgae differ from other phytoplankton groups in having a silicified cell wall, which is the strongest known biological material relative to its density. While it has been suggested that a siliceous wall may have evolved as a mechanical protection against grazing, empirical evidence of its defensive role is limited. Here, we experimentally demonstrate that grazing by adult copepods and nauplii on diatoms is approximately inversely proportional to their silica content, both within and among diatom species. While a sixfold increase in silica content leads to a fourfold decrease in copepod grazing, silicification provides no protection against protozoan grazers that directly engulf their prey. We also found that the wall provides limited protection to cells ingested by copepods, since less than 1% of consumed cells were alive in the faecal pellets. Moreover, silica deposition in diatoms decreases with increasing growth rates, suggesting a possible cost of defence. Overall, our results demonstrate that thickening of silica walls is an effective defence strategy against copepods. This suggests that the plasticity of silicification in diatoms may have evolved as a response to copepod grazing pressure, whose specialized tools to break silicified walls have coevolved with diatoms.